Rare Case of Squamous Cell Cancer – Mixed Neuroendocrine Neoplasm in the tubular Esophagus (MiNEN) discovered by Endoscopic Submucosal Dissection of the entire Tumor - Werner, Christoph R.; Benzler, Katrin; Amsberg, Lisa; Bitzer, Michael; Büringer, Karsten; Gani, Cihan; Overkamp, Mathis; Schempf, Ulrike; Wichmann, Dörte; Malek, Nisar P.; Bösmüller, Hans (Zeitschrift für Gastroenterologie, 2025)
Mixed neuroendocrine-non-neuroendocrine neoplasms (MiNENs) are rare in the gastrointestinal tract.We report the case of a patient in whom complete endoscopic resection of a tumorous lesion in the tubular esophagus, initially diagnosed as squamous cell carcinoma (SCC) led to the diagnosis of SCC-MiNEN, which changed the patient´s treatment course.With improvements in endoscopic techniques, we advocate resection of small malignant lesions in the gastrointestinal tract for both curative and diagnostic reasons.
Keywords: MiNEN; mixed neuroendocrine-non-neuroendocrine neoplasm; squamous cell carcinoma (SCC); neuroendocrine carcinoma (NEC); endoscopic submucosal dissection (ESD); Esophagus; neuroendocrine tumor (NET)